Pelimpahan Hak Asuh Anak di bawah Umur Akibat Perceraian (studi kasus Pengadilan Agama Surakarta) - Henryastuti, Oktavia; , Nuswardhani S.H.,S.U; , Septarina Budiwati, S.H.,C.N.,M.H (2015)
The purpose of this study was to determine: (1) consideration of the judge in determining custody of children under the age of divorce; (2) the legal effect of parents of children after divorce. This research is a normative juridical research is a procedure of scientific research to find out the truth based on the logic of the normative science of law. Research carried out in the Religious Surakarta. Data sources using primary data from interviews, observation, and literature study. Data were analyzed using qualitative analysis. The results showed that: (1) Consideration of the judge in determining the transfer of custody of children under the age of divorce is the judge look and emphasizes the psyche of the child, the judge considered Surakarta Islamic Court was in accordance with justice for all parties; (2) The legal consequences Parents to Kids after a divorce is that although the rights of foster children in the hands of his father, but the mother took part in the child maintenance issues.